Penguatan kompetensi pedagogik mahasiswa Tadris Bahasa Inggris melalui pendekatan Communicative Language Teaching (CLT) - Destiani, Nadia (Maliki Interdisciplinary Journal, 2025)
Strengthening pedagogical competence is a crucial aspect for English Education (Tadris Bahasa Inggris) students who are being trained as future professional teachers. Within the framework of modern language instruction, the Communicative Language Teaching (CLT) approach is considered highly relevant because it prioritizes learners’ ability to use language meaningfully in real-life and functional contexts. This study explores how CLT can be applied as an effective strategy to enhance pedagogical competence, particularly in lesson planning, the use of active teaching methods, and the development of authentic assessment practices. Employing a literature review method, the research draws upon TEFL theories, English language education curricula, and prior studies on CLT implementation. The findings suggest that CLT plays a significant role in preparing students to design communicative, interactive, and contextual learning activities. Moreover, CLT improves classroom management, promotes consistent use of the target language, and fosters collaborative learning environments. Consequently, CLT is recommended as a foundation for curriculum design and teacher training programs in English Education departments.